2018
DOI: 10.1016/j.jmmm.2018.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Eu valence transition behavior in the nano form of EuPd2Si2

Abstract: The compound EuPd2Si2 is a well-known fluctuating-valent compound with a largest variation of Eu valence in a narrow temperature interval (around 150 K).The ball-milled form of this compound was investigated to understand the Eu valence behavior in the nanoform. The compound is found to retain the ThCr2Si2-type tetragonal structure after ball-milling leading to a reduction in particle size, typically falling in the range 10 -100 nm. We find that there is a qualitative change in the temperature dependence of ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…As is evident from resonant photoemission studies of EuPd 2 Si 2 divalent Eu is found for the outermost Eu layers irrespective of temperature [7], suggesting different properties at the surface as compared to the bulk. Ball milling EuPd 2 Si 2 into the nanoparticle range leads to a broad distribution of valence transitions and possibly magnetic ordering at temperatures below 8 K [8]. To our knowledge, up to now no thin-film-specific report regarding this ternary compound exists, leaving several questions regarding the coupling between lattice and electronic degrees of freedom unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…As is evident from resonant photoemission studies of EuPd 2 Si 2 divalent Eu is found for the outermost Eu layers irrespective of temperature [7], suggesting different properties at the surface as compared to the bulk. Ball milling EuPd 2 Si 2 into the nanoparticle range leads to a broad distribution of valence transitions and possibly magnetic ordering at temperatures below 8 K [8]. To our knowledge, up to now no thin-film-specific report regarding this ternary compound exists, leaving several questions regarding the coupling between lattice and electronic degrees of freedom unanswered.…”
Section: Introductionmentioning
confidence: 99%